2019
DOI: 10.1371/journal.pntd.0007277
|View full text |Cite
|
Sign up to set email alerts
|

The invasive giant African snail Lissachatina fulica as natural intermediate host of Aelurostrongylus abstrusus, Angiostrongylus vasorum, Troglostrongylus brevior, and Crenosoma vulpis in Colombia

Abstract: Background Several metastrongyloid lungworms are unreported pathogens in Colombia. Angiostrongylus vasorum and Crenosoma vulpis target the cardiopulmonary system of domestic and wild canids. Aelurostrongylus abstrusus and Troglostrongylus brevior infect felids and considering that six wild felid species exist in Colombia, knowledge of feline lungworm infections is important for their conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 63 publications
(113 reference statements)
0
47
0
3
Order By: Relevance
“…Table 2 provides the measurements of all developmental stages of the nematode species reported here in comparison with previously reported data [ 10 , 28 , 29 , 31 , 32 , 34 36 , 38 , 39 , 46 , 48 50 ].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Table 2 provides the measurements of all developmental stages of the nematode species reported here in comparison with previously reported data [ 10 , 28 , 29 , 31 , 32 , 34 36 , 38 , 39 , 46 , 48 50 ].…”
Section: Resultsmentioning
confidence: 95%
“… a References [ 10 , 28 , 29 , 32 , 34 , 46 48 ] b References [ 31 , 35 , 36 ] c References [ 10 , 28 ] d References [ 38 , 39 ] e Reference [ 44 ] Abbreviations : E, experimental infection; N, natural infection; P, present study (number of larvae measured); nv, not visible; nr, not reported; L2, second stage larvae; L3, third-stage larvae …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…could possibly be shared. Co-infection of cardiorespiratory parasites in intermediate hosts was reported by Lange et al (2018) and Penagos-Tabares et al (2019) , finding larvae of two metastrongyloid species in the same slug. Thus, intermediate hosts with mixed infections could be eaten by paratenic hosts and then be transmitted to guignas.…”
Section: Discussionmentioning
confidence: 76%
“…However, T . brevior was found in Colombia and Austria [ 88 , 94 ] as well as Greece [ 69 ]. These results are surprising, as T. brevior has never been found in felids from South America or Austria.…”
Section: Felids Parasites and (Bio)geographymentioning
confidence: 99%